2017
DOI: 10.1080/09168451.2016.1234928
|View full text |Cite
|
Sign up to set email alerts
|

Rim15 and Sch9 kinases are involved in induction of autophagic degradation of ribosomes in budding yeast

Abstract: Autophagic degradation of ribosomes is promoted by nutrient starvation and inactivation of target of rapamycin complex 1 (TORC1). Here we show that selective autophagic degradation of ribosomes (called ribophagy) after TORC1 inactivation requires the specific autophagy receptor Atg11. Rim15 protein kinase upregulated ribophagy, while it downregulated non-selective degradation of ribosomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…This starvation response is thought to scavenge cellular macromolecules and organelles to recycle cellular building blocks (Reggiori and Klionsky, 2013), but reduction in the concentration of ribosomes has also been proposed as a function for these pathways (Tsukada and Ohsumi, 1993). In accordance with this latter idea, mutations in the autophagy genes ATG1, ATG13 and ATG17 and the ribophagy gene RIM15 (Waliullah et al, 2017) all showed significant epistasis with rapamycin treatment (figure 3A, right).…”
Section: Mtorc1 Controls Cytoplasmic Rheology By Tuning Ribosome Concmentioning
confidence: 76%
See 1 more Smart Citation
“…This starvation response is thought to scavenge cellular macromolecules and organelles to recycle cellular building blocks (Reggiori and Klionsky, 2013), but reduction in the concentration of ribosomes has also been proposed as a function for these pathways (Tsukada and Ohsumi, 1993). In accordance with this latter idea, mutations in the autophagy genes ATG1, ATG13 and ATG17 and the ribophagy gene RIM15 (Waliullah et al, 2017) all showed significant epistasis with rapamycin treatment (figure 3A, right).…”
Section: Mtorc1 Controls Cytoplasmic Rheology By Tuning Ribosome Concmentioning
confidence: 76%
“…The steady-state concentration of ribosomes in the cytoplasm is determined by the rate of ribosomal production, which is strongly affected by the SIT4 and SFP1 genes (Peterson et al, 1999b), and the rate of ribosomal degradation. Ribosomes are usually quite stable, but starvation conditions can drive autophagy and ribophagy to accelerate rates of ribosome degradation, especially when mTORC1 is inhibited (Waliullah et al, 2017). This starvation response is thought to scavenge cellular macromolecules and organelles to recycle cellular building blocks (Reggiori and Klionsky, 2013), but reduction in the concentration of ribosomes has also been proposed as a function for these pathways (Tsukada and Ohsumi, 1993).…”
Section: Mtorc1 Controls Cytoplasmic Rheology By Tuning Ribosome Concmentioning
confidence: 99%
“…Ribosomes are usually quite stable, but starvation conditions can drive autophagy and ribophagy to accelerate ribosome degradation, especially when mTORC1 is inhibited (Waliullah et al, 2017). This starvation response is thought to scavenge macromolecules and organelles to recycle cellular building blocks, but reduction in the concentration of ribosomes has also been proposed as a function for these pathways (Tsukada and Ohsumi, 1993).…”
Section: Mtorc1 Controls Cytoplasmic Rheology By Tuning Ribosome Concmentioning
confidence: 99%
“…Ribophagy is a specific autophagic response targeting ribosomes. In yeast, ribophagy involves ribosomal de‐ubiquitination by the mRNA‐binding ubiquitin‐specific protease Ubp3 and its cofactors Bre5, Doa1 (also known as Ufd3), and Cdc48 (Kraft et al , ; Ossareh‐Nazari et al , ) and requires Atg11 (Waliullah et al , ). Conversely, the autophagic removal of dispensable ribosomes is negatively regulated by listerin E3 ubiquitin‐protein ligase 1 (Ltn1)‐dependent ubiquitination (Ossareh‐Nazari et al , ), and possibly by NEDD4 family E3 ubiquitin‐protein ligase Rsp5 (Shcherbik & Pestov, ).…”
Section: Introductionmentioning
confidence: 99%